Monitoramento de mudas em plantio para restauração ecológica em área de floresta ombrófila densa - Vicentin, Alessandra (Universidade Federal de São Carlos, 2015)
The Atlantic Forest is considered hotspot for biodiversity conservation, due to its high biological diversity, high endemism and high threat of degradation. This scenario has raised concern about finding information to support recovery projects of degraded areas. This study aimed to evaluate the growth, coverage percentage in the soil and the survival of species of the Atlantic Forest, from the planting seedlings in different treatments, present in a particular area in the recovery process, in the region Vale do Ribeira, located in Sete Barras, Brazil. In 2004, the owner made the removal of vegetation for grazing deployment with brachiaria. In 2009, UFSCar was sought to implement the project of "experimental recovery of degraded areas" where seedlings were planted, divided into spacing of 1.5 x 2 m (dense treatment) and 3 x 2 m (conventional treatment). In this study, from July 2013 was carried out monitoring of the area to assess the growth and survival of planted seedlings as well as the percentage of shading and grasses. Five surveys were conducted (July 2013, October 2013, January 2014, April 2014 and July 2014) to evaluate the survival and growth (height, stem diameter and crown diameter) of the seedlings. 30 months after planting, the 220 individuals initially raised in this study, the survival was 85.2% in the dense treatment and 84.8% in the conventional treatment, so mortality was around 15% for both treatments. The species with the highest average growth in height were Croton floribundus, Cytharexyllum solanaceum, Casearia gossypiosperma, Croton urucurana, Colubrina glandulosa, Lafoensia pacari, Inga marginata e Myrsine guianensis. The species with the highest average growth in stem diameter were Acnistus arborescens, Croton urucurana, Apeiba tibourbou, Croton floribundus, Inga marginata, Campomanesia xanthocarpa, Colubrina glandulosa and Lafoensia pacari. The species with the highest average growth in crown diameter were Croton urucurana, Croton floribundus, Cytharexyllum solanaceum, Acacia polyphyla, Colubrina glandulosa, Inga marginata, Lafoensia pacari and Rhamnidium elaeocarpum. As for the percentage coverage in the soil and grasses, there was significant difference in the dense and conventional treatment compared to witness. It is concluded that the above species are indicated for use in future restoration projects in areas of Rain Forest. Both treatments showed greatest shading (in comparison with witness) at the end of the monitoring period, thereby enabling a reduction of exotic grasses. However, in dense treatment was no shading and greater control of grasses. Thus, it can be concluded that at higher cost of implementation and the similar results, the dense treatment was not recommended thickened in the region.
Seedling monitoring in planting for restoration ecology in Dense Rainforest area
Keywords: Biodiversidade; Biodiversity; Ecologia das florestas tropicais; Rain forest ecology; Proteção ambiental; Environmental protection; Restauração florestal; Forest restoration; Mata Atlântica (Brazil); CIENCIAS BIOLOGICAS::ECOLOGIA::ECOLOGIA DE ECOSSISTEMAS